UPAYA KEPOLISIAN DALAM MENGATASI TINDAK KEJAHATAN AKIBAT MINUMAN KERAS DI KOTA SEMARANG (Studi Kasus Di Polwiltabes Semarang) - Andri Winjaya Laksana (UNISSULA, 2014)
Consuming liquor cause a variety of social ills, gave birth to various forms of bad deviation in behavior, morals, religion, psychology, and health. Liquor can be said is the embryo of a crime, because when a person is under the influence of liquor has a tendency to commit crimes, such as persecution, robbery, theft, extortion and even murder. The research method in this study is that sociological juridical procedures used to solve research problems by examining the secondary data in the form of regulations applicable law was followed by conducting research on primary data in the field. The results obtained in the policing effort in tackling crime due to alcohol, among others, include pre-emtive efforts, preventive measures and repressive efforts while the obstacles that arise in police efforts to tackle crime due to alcohol because there is no tradition of drinking to celebrate an event in some areas such as in a wedding or a traditional ceremony, police officers who act irresponsible that protect dealers and sellers of liquor, there is no legislation that specifically regulates the liquor, the absence of strict sanctions for traffickers, sellers, and buyers of liquor that exceeds the prescribed standards, and the lack of participation of the community to participate in tackling abuse of liquor.